Ceticismo e subjetividade em Descartes - Zanette, Edgard Vinicius Cacho (2011)
The methodical doubt enables the discovery of the first certainty of cartesian philosophy, the cogito. The cogito is discovered, not invented. For this intrinsic characteristic of the cartesian method, and to understand the cogito we have to pass through the most radical hyperbolic doubt. The cartesian doubt puts in motion continuous process that destroys all and any opinion that contains the slightest hint of doubt. In a first moment in this process of destruction of de losses, the methodical doubt propose abandonment of the external external world instead subject meditador, because the senses deceive, and all that, somehow, expect them to exist is considered doubtful, and therefore uncertain. The rigor of this review proposed by Descartes will, however, later, developed another separation between the subject of de doubt and everything external to it. This second stage is the most dramatic and radical the cartesian thought, because is through him that there will be conditions of possibility to the cogito to be discovered and sensed, as the fist certainly in the order of the Meditations. Despite this dramatic context that cogito appears, the problem of the external world dont's contributes only to the discovery of the cogito, but the problem of the external world will reappear solved by the cogito, when destroyed the possibility of doubt and the overall failure of reason. Is about this first movement of the emergence of the problem from the external world, its development and it's overcoming whit the discovery of the cogito that emerges what we call the subject or subjectivity in Descartes. Therefore, we will investigate this discovery process of cogito, via methodical doubt, where skepticism is reinvented by Descartes as the firt moment of the serch for truth, such that the problem of the external world emerges as the condition of the destruction of the losses for the discovery at least one indubitable truth. After the cartesian doubt, as the sense and the complement of the same, we have the birth of the cartesian notion of subject or subjectivity. Against this notion we will investigate that constitutes the first moment of subjet discovery or cartesian subjectivity centered in the cogito, wich we shall call the metaphysical subject.